Nota sobre o encontro de Aedes aegypti em bromélias Finding of Aedes aegypti breeding in bromeliad - Oswaldo Paulo Forattini; Gisela Rita Alvarenga Monteiro Marques (Universidade de São Paulo, 2000)
Descreve-se o encontro de formas imaturas de Aedes aegypti em bromélia domesticada para fins decorativos. São feitas considerações sobre as implicações desse encontro para o controle desse mosquito. A breeding place of Aedes aegypti immature forms were found in bromeliads domesticated for decorative purposes. Implications for the control measures were considered.